Benson's relaxation effect in comparing to systematic desensitization on anxiety of female nurses: A randomized clinical trial - Mahbobeh Sajadi; Khatereh Goudarzi; Sharareh Khosravi; Molod Farmahini-Farahani; Abolfazl Mohammadbeig (Indian Journal of Medical and Paediatric Oncology)
Introduction: Nursing staffs expose to a high level of anxiety. This study aimed to compare the effect of Benson's relaxation and systematic desensitization methods for decreasing the anxiety score of nurses. Materials and Methods: In a randomized clinical trial, 72 female nurses were assigned randomly to three different groups. Benson's relaxation and systematic desensitization were used as intervention beside control group. After intervention, the Spielberger state-trait anxiety inventory was used for measuring the anxiety score. Analysis of variance (ANOVA), Tukey test, and paired t-test were applied for comparing three group scores. Results: The ANOVA test showed that a significant difference among three groups regarding scores of posttrait and poststate anxiety (P < 0.05). The Tukey test showed that both Benson's relaxation and systematic desensitization methods were effective in decreasing of the anxiety score of nurses. Moreover, the mean change in trait and state anxiety scores at Benson's relaxation and systematic desensitization groups was more than control group, respectively, and was statistically significant. Conclusion: Both Benson's relaxation and systematic desensitization methods are effective in improvement of the state and trait dimensions of anxiety. However, these methods could be applied in stressful situation among medical staffs of students.